Financial Feasibility Analysis of Chocolate Spread with Coconut Ingredients as Agroindustrial Product - Dyah Ayu Savitri; Herlina Herlina; Noer Novijanto (Journal La Bisecoman, 2021)
Chocolate spread is a type of paste which is mostly spread on breads and pastries. This research was conducted by calculating financial feasibility of chocolate spread with addition of coconut flour and coconut sugar produced by Yayasan Suren untuk Indonesia. The aim of this research is to observe the financial feasibility of chocolate spread with addition of coconut flour and coconut sugar in order to obtain its development strategy on production management and marketing. The results showed BEP value of 16659,4; PBP (year) value of 1,9; NPV value of 20389635,9; IRR value of 1526% and B/C ratio of 1,05. Therefore, based on financial feasibility analysis, this business is feasible to execute. Furthermore, based on sensitivity analysis using four scenarios, this business is not feasible to execute while undergoes increasing of price of raw material as big as 4% and decreasing of selling price as big as 3%. Based on those scenario, NPV value of this business was Rp -194.353.160,28 (<0); followed by value of IRR, Net B/C, payback period and BEP were 10,94%; 1,00; 7,88 and 155.020,62 respectively.